MEDIA SOSIAL (INSTAGRAM) UNTUK PEMBELAJARAN: STUDI PADA PENDIDIKAN D3 KEBIDANAN - Erika Agung Mulyaningsih (Jurnal Ilmiah Kesehatan Media Husada, 2022)
Changes in the educational process due to the Covid-19 pandemic pose challenges for lecturers and students, the problems of online learning is a decrease in student understanding, boredom during learning and lack of motivation to be able to complete learning and assignments properly. The purpose of this research is to overcome learning problems in Basic Socio-Cultural Courses through the use of Social Media This research is a Classroom Action Research conducted in 3 cycles, each cycle consists of 2 x 100 minutes of face-to-face and 2x 120 minutes of structured assignments, so a total of 6 x 100 minutes of face-to-face and 6 x 120 structured tasks. The subjects of this study were students in the second semester of the 2020/2021 academic year, totaling 17 people. The research was conducted from April 1 to May 17, 2021. The results of this study have a good impact on student learning outcomes scores, learning satisfaction because it is very interesting and not boring and is able to lead students to think critically and have broad knowledge. The minimum grade score is 60; the maximum grade score is 91.8; the mean score was 86.7; and a median of 90.7. The use of social media in learning must be relevant to the topic and Care is needed in choosing social media accounts to avoid news that cannot be justified.